Dramaturgia pojęć - Krajewska, Anna (Przestrzenie Teorii, 2021)
The article is an introduction to the dramaturgies in contemporary humanities and focuses on the problem of the dramaturgy of concepts. Using Olga Tokarczuk’s example of the “tender narrator” and Wisława Szymborska’s poem Night, it shows different ways of creating attitudes towards the disintegration of the vision of the world based on the topos of the Book.